Simulation and analysis of chest loads on crews during Lunar-Earth re-entry returns - Wang, Jiatao; Peng, Zhiyong; Yao, Yongjie; Zhou, Qianxiang; Guo, Pan (Frontiers in Bioengineering and Biotechnology, 2024)
The safety of crews is the primary concern in the manned lunar landing project, particularly during reentry as the manned spacecraft returns from a direct Lunar-Earth trajectory. This paper analyzed the crew's chest biomechanical response to assess potential injuries caused by acceleration loads during the re-entry phase. Initially, a sophisticated finite element model of the chest was constructed, whose effectiveness was verified by experiments involving vertebral range of motion, rib lateral rupture, and chest frontal impact. The model was then subjected to the return re-entry loads simulating the Apollo and Chang'e 5 T1 (CE-5T1) test returner to specifically analyze the correlation between the acceleration load and the injury of the crew's chest tissues and organs. The results indicate that the biomechanical response of crew chest bone tissue under the two return missions is within the threshold value and will not directly cause damage. Compared to the Apollo mission, the CE-5T1 mission's load poses a higher risk to internal organs. These findings can enhance the crew's safety and provide reliable assurance for future space exploration.